O PAPEL DO PROGRAMA BOLSA FAMÍLIA NA ESCOLARIZAÇÃO DE JOVENS UNIVERSITÁRIOS DA EDUCAÇÃO BÁSICA AO ENSINO SUPERIOR - SUELLEN MARIA MONTEIRO ROSA MARCOS (2023)
This dissertation is linked to the of research: Policies, educational practices and social exclusion/inclusion of the Graduate Program Master in Education at the Federal University of Mato Grosso do Sul - Campus do Pantanal. The general objective of the work addresses the relationship between the Bolsa Família Program (PBF) and the enrollment of students from poor families in higher education. The PBF was created in 2003 during the presidency of Luiz Inácio Lula da Silva with the aim of protecting vulnerable families through conditional cash transfers. Among the studies of the program, we highlight the reduction of poverty indicators, the empowerment of women who receive the benefit, the increase in access to health services for the poor, and the extension of schooling for children and adolescents from beneficiary families. While recognizing the importance of these results, we conducted research focused on the extension of studies for program beneficiaries. We reviewed specialized literature to understand the impact of the PBF on the education of children and adolescents who receive the benefit. Through a case study, we investigated perceptions about the PBF formulated by higher education students who received the benefit while attending basic education. The case study included a group of students from the Pedagogy Teacher Education Program at the Federal University of Mato Grosso do Sul, Pantanal Campus. Finally, we emphasize that the silence of the University regarding poverty and inequalities needs to be rethought. We believe that the discussion about the intentions and results of public policies aimed at fighting poverty and promoting equality is necessary and healthy. And, in this sense, we believe that this Dissertation offers a modest contribution for the discussion to gain shape and consistency. Keywords: Bolsa Família Program, higher education, pedagogy, extension of studies.